Cross-sectional investigation and correlation analysis of psychology of college students returning to campus after COVID-19 lockdown lift - Wang, Zhifeng; Jiang, Bing; Wang, Xingtong; Niu, Yi; Xue, Haihong (Frontiers in Psychiatry, 2022)
Objective To conduct a large cross-sectional survey of the mental health of college students during the recovery period of the COVID-19 epidemic. Methods Symptom Checklist 90 (SCL-90) and COVID-19 questionnaire were used to investigate the overall mental health level and cognition of epidemic situation of college students in seven colleges and universities in Shaanxi Province. Results (1) In the recovery period of COVID-19 epidemic, college students still had psychological and somatic symptoms such as obsessive-compulsive disorder, interpersonal sensitivity, anxiety, hostility, and poor appetite or insomnia; (2) female college students, science and engineering college students, freshmen and senior graduates, and some ethnic minority college students were all groups with psychological symptoms; (3) the psychological status of college students was related to their perception of COVID-19 epidemic, and the more knowledge about epidemic prevention and control, the more confident they were in overcoming the epidemic, and the milder the psychological symptoms. Conclusion College students still have some mental health problems in the recovery period of COVID-19 epidemic, which should be paid attention to by education authorities and colleges and universities.